Pazopanib plus best supportive care versus best supportive care alone in advanced gastrointestinal stromal tumours resistant to imatinib and sunitinib (PAZOGIST): a randomised, multicentre, open-label phase 2 trial. Issue 5 (May 2016) - Mir, Olivier; Cropet, Claire; Toulmonde, Maud; Cesne, Axel Le; Molimard, Mathieu; Bompas, Emmanuelle; Cassier, Philippe; Ray-Coquard, Isabelle; Rios, Maria; Adenis, Antoine; Italiano, Antoine; Bouché, Olivier; et al.
Summary: Background: Gastrointestinal stromal tumours (GIST) are the most common mesenchymal neoplasms of the gastrointestinal tract. Imatinib followed by sunitinib and regorafenib is the standard sequence of treatment for advanced disease. Pazopanib is effective in soft tissue sarcomas but has never been assessed in advanced GIST in a randomised trial. We aimed to assess the efficacy and safety of pazopanib in patients with previously treated advanced GIST. Methods: In this randomised, open-label phase 2 study, we enrolled adults (aged ≥18 years) with advanced GIST resistant to imatinib and sunitinib from 12 comprehensive cancer centres or university hospitals in France and randomly assigned them 1:1 using an interactive web-based centralised platform to 800 mg oral pazopanib once daily in 4-week cycles plus best supportive care or best supportive care alone. Randomisation was stratified by the number of previous treatment regimens (2 vs ≥3); no-one was masked to treatment group allocation. Upon disease progression, patients in the best supportive care group were allowed to switch to pazopanib as compassionate treatment. The primary endpoint was investigator-assessed progression-free survival, analysed by intention-to-treat. All randomised participants who received at least one dose of pazopanib were included in the safety analysis. This study is registered withClinicalTrials.gov, numberNCT01323400 . Findings: Between April 12, 2011, and Dec 9, 2013, 81 patients were enrolled and randomly assigned to pazopanib plus best supportive care (n=40) or best supportive care alone (n=41). The median follow-up was 26·4 months (IQR 22·0–37·8) in the pazopanib plus best supportive care group and 28·9 months (22·0–35·2) in the best supportive care group. 4-month investigator-assessed progression-free survival was 45·2% (95% CI 29·1–60·0) in the pazopanib plus best supportive care group versus 17·6% (7·8–30·8) in the best supportive care group (hazard ratio [HR] 0·59, 95% CI 0·37–0·96; p=0·029). Median progression-free survival was 3·4 months (95% CI 2·4–5·6) with pazopanib plus best supportive care and 2·3 months (2·1–3·3) with best supportive care alone (HR 0·59 [0·37–0·96], p=0·03). 36 (88%) of the patients originally assigned to the best supportive care group switched to pazopanib following investigator-assessed disease progression; these patients had a median progression-free survival from pazopanib initiation of 3·5 months (95% CI 2·2–5·2). 55 (72%) of the 76 pazopanib-treated patients had pazopanib-related grade 3 or worse adverse events, the most common of which was hypertension (15 [38%] in the pazopanib plus best supportive care group and 13 [36%] in the best supportive care group). 20 (26%) patients had pazopanib-related serious adverse events (14 [35%] in the pazopanib plus best supportive care group and six [17%] in the best supportive care group), including pulmonary embolism in eight (9%) patients (five [13%] in the pazopanib plus best supportive care group and three [7%] in the best supportive care group). Three pazopanib-related deaths occurred (two pulmonary embolisms [one in each group] and one hepatic cytolysis [in the best supportive care group]). Three adverse event-related but not pazopanib-related deaths occurred in the best supportive care group after switch to pazopanib; these deaths were from hyperammonaemic encephalopathy, pneumopathy, and respiratory failure. Interpretation: Pazopanib plus best supportive care improves progression-free survival compared with best supportive care alone in patients with advanced GIST resistant to imatinib and sunitinib, with a toxicity profile similar to that reported for other sarcomas. This trial provides reference outcome data for future studies of targeted inhibitors in the third-line setting for these patients. Funding: GlaxoSmithKline, French National Cancer Institute, EuroSARC (FP7-278742), Centre Léon Bérard.